Approximate convexity principles and applications to PDEs in convex domains. (March 2020) - Bucur, Claudia; Squassina, Marco
Abstract: We obtain approximate convexity principles for solutions to some classes of nonlinear elliptic partial differential equations in convex domains involving approximately concave nonlinearities. Furthermore, we provide some applications to some meaningful special cases.